Propuesta de mejora de producción en la obtención de bloques de balsa en la empresa Agro industria Balsera S. A., ubicada en el cantón Ventanas Km 3 vía a Quevedo - Méndez Santana, Wilmer Reinaldo (2016)
Nowadays all the companies that want to continue maintaining a good competitiveness within their activities must adapt to the necessities that arise every day, to face these factors it is necessary the strengthening of all the productive activities the analysis and the evaluation in the company AGROINDUSTRIA BALSERA S.A, allows the generation of proposals to improve and help the mitigation or eradication of elements, actions that cause any kind of inconveniences such as: unproductive times, economic losses, damage to facilities etc., even if the activities of a company can Develop and meet the proposed objective there will always be a better way or method of performing an operation. The main technique applied for this research was in situ observation, giving way to the identification and evaluation of internal and external factors that affect or help every aspect of the company, the application of a SWOT matrix is fundamental to know the advantages and Competitive disadvantages, emphasizing the development of production through flow diagrams that facilitate the detail of the activities, for the full utilization of the physical structure with which it is counted, when setting an evaluation of the maintenance applied to the area of production by Medium of a criticality matrix will determine the critical points or sites that can exist in the process facilitating the taking of corrective actions and the generation of preventive measures eliminating the areas that are in the area of criticality, the economic control that allows the calculation of the cost Of production and determination of values that can be reduced once all corrective actions have been implemented to improve the process, a suitable working environment will be granted for the development and growth of the balsa block manufacturing activity, increasing its economic, Control and management.